Strategies for SME Digital Ecosystem in Indonesian Metal Industry - Yudianto, Bernadinus; Trilaksono, Teddy; Setiawati, Isti Budhi; Wijanarti, Sri Widya; Suhartanto, Eko (Universitas Prasetiya Mulya, 2022)
SMEs can achieve the paradigm shift they need for development by creating a business ecosystem that will improve their skills and technicalities through digital media. This study aims to identify several strategies that can influence changes in the digital ecosystem development for SMEs in Indonesia to help them survive and be sustainable. This research focuses on a single case study approach. Citeureup metal industry centre was chosen by involving 70 SMEs spread across the Citeureup area. This study found that four strategies can be applied to develop a digital ecosystem. The first is helping SMEs to level up, and the second is connecting with the surrounding stakeholders. The third is to help SMEs expand their market, and the last is to help them build regeneration strategies.